Technological Innovations and their Impact on Pharmaceutical Industry: An Empirical Study of Medical Representatives - CHANDRA, KOMAL (International Journal of Psychosocial Rehabilitation, 2021)
The pharmaceutical industry’s unique company model and commercial operations have a notable impact on the process of delivering new drugs to patients, even though they are not widely comprehended outside of the industry. The likelihood of a new drug succeeding could be higher, and the process is very time-consuming, costly, and hazardous. After implementing international patent rules on January 1st, 2005, the Indian Pharmaceutical Industry saw a tremendous shift. India’s indigenous pharmaceutical businesses have seen massive growth in R & D investment to remain competitive in the global pharmaceutical industry. India has very well researchers, a well-established computer industry, and technology for producing bulk pharmaceuticals and formulations, despite the country’s limited pharmaceutical market and lack of financing for drug development initiatives. Following a discussion of the company’s commercial realities and restrictions, along with its current issues, there follows an examination of some of the expected future commercial and technological advances in the company.